2022
DOI: 10.1007/s00467-022-05439-y
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro measurements of ultrafiltration precision in hemofiltration and hemodialysis devices used in infants

Abstract: Background To determine in vitro whether infant hemofiltration and hemodialysis devices can reliably deliver precise ultrafiltration (UF) control. Methods We tested the Prismaflex, Aquarius and NIDUS devices which have different circuit types, by in vitro testing with a bag of saline set up as a dummy patient, and monitoring fluid shifts by precise weighing. We looked for differences between the UF rates set and achieved and between the UF result the devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Our data also confirm that while it is easy to accurately measure the UF obtained by PD, it is frequently difficult to predict or control. These UF results are in concordance with previous clinical compassionate use of NIDUS, as well as animal and in vitro testing (11,13). The higher biochemical clearances of NIDUS compared with PD also reflect previous findings (11), but this is the first comparison between CVVH (Prismaflex and Aquarius) and NIDUS.…”
Section: Discussionsupporting
confidence: 89%
“…Our data also confirm that while it is easy to accurately measure the UF obtained by PD, it is frequently difficult to predict or control. These UF results are in concordance with previous clinical compassionate use of NIDUS, as well as animal and in vitro testing (11,13). The higher biochemical clearances of NIDUS compared with PD also reflect previous findings (11), but this is the first comparison between CVVH (Prismaflex and Aquarius) and NIDUS.…”
Section: Discussionsupporting
confidence: 89%
“…Our device was built for blood flows of 75-120 mL/min (subjects with weight of 20-40 kg), which are compatible with blood flows used in adult patients with severe AKI care. High pressures in the dialysis filter fluid compartment are associated with higher UFnet errors in many currently used CRRT machines [35]; however, an afferent and efferent fluid bag weight variation as a servo-controlled mechanism is associated with a very low error in UFnet in children [35,36]. In this way, our device was able to compensate for a very high filter dialysate chamber pressure (150 mmHg).…”
Section: Discussionmentioning
confidence: 91%
“…This machine requires a 5-ml priming volume (plus stroke volume) and can be used with a 0.045-m 2 filter, setting a dialysate flow rate in the range of 0-400 ml per hour and an UF rate in the range of 0-60 ml per hour. A recent study by Crosier et al has shown that, when used in small infants, two modern CKRT devices with conventional circuits, the Prismaflex and Aquarius, do not have the capacity to deliver precise or reliable UF, or to record its volume correctly even when they are set to produce zero UF, but the NIDUS volumetrically controlled circuit does [26]. A clinical study is currently active in the UK to evaluate efficacy, safety, and outcomes of the NIDUS machine as compared with the other existing KRT methods for children who weigh < 8 kg.…”
Section: Extraordinary Researchmentioning
confidence: 99%
“…The new dialysis devices were initially used in patients in whom PD was contraindicated or proved ineffective, with adequate results on clearance, fluid removal, and safety. Clinicians quickly realized the versatility and precision of these extracorporeal treatments, which provided greater dialysis efficiency than PD and allowed for fluid management planning [25,26,33]. It is well-known that, in critically ill children with AKI, the amount of fluid overload has an almost linear association with mortality [34].…”
Section: Adoption Of a New Paradigmmentioning
confidence: 99%